Relations between Risk for Sleep-Disordered Breathing, Cognitive and Executive Functioning, and Academic Performance in Six-Year-Olds. Issue 7 (3rd October 2019) - Luo, Rebekah; Harding, Rebecca; Galland, Barbara; Sellbom, Martin; Gill, Amelia; Schaughency, Elizabeth
ABSTRACT: Research Findings : Optimal sleep is important for children's learning and development. Sleep disordered breathing (SDB) refers to a spectrum of conditions from simple snoring to obstructive sleep apnea that is common in childhood and interrupts sleep. We examined pathways between SDB and academic performance of children ( N = 163, M age = 6.2 years) one year after school entry. Measures included parent questionnaire and clinical assessment of SDB, standardized tests and rating scales of cognitive and executive functioning, researcher-administered literacy and numeracy tasks, and teacher-reported academic performance. Structural equation modeling (SEM) revealed direct and indirect paths between SDB and poorer academic performance. In indirect models, children's SDB severity score was significantly linked to poorer executive functioning (β = .38, p < .01) and negatively associated with nonverbal reasoning (β = −.21, p < .01). Poorer executive functioning, in turn, was negatively related to the verbal composite (β = −.61, p < .01), with verbal and nonverbal composites associated with academic performance (βs = .56, .27, respectively, p 's < .01). Practice or Policy : These findings point to the need for attention to SDB and its links to potential cognitive sequelae across early development. Practitioners equipped with knowledge of SDB symptoms can facilitate referral for appropriate consultation and evaluation.